Empowering Social Workers : Virtuous Practitioners - Pawar, Manohar; Hugman, Richard; Alexandra, Andrew; Anscombe, A. W. (Bill) (Springer Singapore : Imprint: Springer, 2017)
This book demonstrates the central role of ethical character in effective social work practice. Showcasing select biographies of social workers, it reveals how skilled practitioners have developed such core virtues as compassion, love, commitment, prudence, respect for human dignity and a critical sense of social justice through the course of their working lives, and how they apply these virtues in a wide variety of settings and situations to enhance the well-being of the people and communities they work with. As such, the book offers a powerful and inspiring resource to help educators, students and practitioners understand the unbreakable link between what social workers and other social welfare and social development professionals do and who they are, and thereby cultivate core qualities that should be promoted. "Pawar, Hugman, Alexandra and Anscombe have found a novel and creative way to explore virtues in social work by examining the career contributions of a group of social work practitioners engaged in 'virtuous action'. Their stories are inspiring and they provide much-needed role models for students and practitioners embarking on empowering practice" - Dr. Mel Gray, Professor of Social Work, The University of Newcastle. New South Wales, Australia. "In an age where the virtues of truth, cooperation and "doing the right thing" are increasingly being eroded in public life, this book serves as both an inspiration and invaluable resource to all social work practitioners seeking to reflect on, and improve their practice" - Dr. Martin Ryan, Social Worker, Counsellor/Community Educator, Jesuit Social Services, Melbourne. "The editors are to be commended for examining the virtuous characters of these ten professional social workers. The use of detailed biographies is an innovative and important approach which helps us to appreciate just what a tremendous impact the virtues can have." - Dr. Christian B. Miller, A. C. Reid Professor of Philosophy, Director, The Character Project, Wake Forest University, USA.
Keywords: Social sciences.; Public health.; Social work.; Social service.; elektronické knihy; electronic books